Iron-Based Microbial Ecosystem on and Below the Seafloor: A Case Study of Hydrothermal Fields of the Southern Mariana Trough - Kato, Shingo; Nakamura, Kentaro; Toki, Tomohiro; Ishibashi, Jun-ichiro; Tsunogai, Urumu; Hirota, Akinori; Ohkuma, Moriya; Yamagishi, Akihiko (Frontiers in Microbiology, 2012)
Microbial community structures in deep-sea hydrothermal vents fields are constrained by available energy yields provided by inorganic redox reactions, which are in turn controlled by chemical composition of hydrothermal fluids. In the past two decades, geochemical and microbiological studies have been conducted in deep-sea hydrothermal vents at three geographically different areas of the Southern Mariana Trough (SMT). A variety of geochemical data of hydrothermal fluids and an unparalleled microbiological dataset of various samples (i.e., sulfide structures of active vents, iron-rich mats, borehole fluids and ambient seawater) are available for comparative analyses. Here, we summarize the geochemical and microbiological characteristics in the SMT and assess the relationship between the microbial community structures and the fluid geochemistry in the SMT by thermodynamic modeling. In the high-temperature vent fluids, aerobic sulfide-oxidation has the potential to yield large amounts of bioavailable energy in the vent fluids, which is consistent with the detection of species related to sulfide-oxidizing bacteria (such as Thiomicrospira in the Gammaproteobacteria and Sulfurimonas in the Epsilonproteobacteria). Conversely, the bioavailable energy yield from aerobic iron-oxidation reactions in the low-temperature fluids collected from man-made boreholes and several natural vents were comparable to or higher than those from sulfide-oxidation. This is also consistent with the detection of species related to iron-oxidizing bacteria (Mariprofundus in the Zetaproteobacteria) in such low-temperature samples. The results of combination of microbiological, geochemical and thermodynamic analyses in the SMT provide novel insights into the presence and significance of iron-based microbial ecosystems in deep-sea hydrothermal fields.